2014
DOI: 10.1021/ef4020422
|View full text |Cite
|
Sign up to set email alerts
|

Study of Oxy-fuel Coal Combustion in a 0.1 MWth Circulating Fluidized Bed at High Oxygen Concentrations

Abstract: The combustion and emission characteristics under three kinds of firing modes [O 2 /N 2 , O 2 /CO 2 , and O 2 / recycled flue gas (RFG)] at high oxygen concentrations were investigated in a 0.1 MW th circulating fluidized-bed combustion system. The 0.1 MW th circulating fluidized-bed combustion unit was built in 2010 and retrofitted to use RFG in 2012, which was specially designed for combustion at high oxygen concentrations (up to 55%). The experimental results showed that CO 2 concentrations in the flue gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although other authors observed that even though NOx concentration is higher for oxy‐fuel combustion, fuel‐N conversion to NOx is generally lower under oxy‐fuel than air combustion. Conversely, Li et al found that both NOx concentration and fuel‐N conversion were lower under oxy‐fuel. The operating condition of these studies are typically the same, with operating temperatures ranging from 850 to 950 °C and at an average O 2 oxidant concentration of 21%.…”
Section: Design and Operational Issuesmentioning
confidence: 96%
“…Although other authors observed that even though NOx concentration is higher for oxy‐fuel combustion, fuel‐N conversion to NOx is generally lower under oxy‐fuel than air combustion. Conversely, Li et al found that both NOx concentration and fuel‐N conversion were lower under oxy‐fuel. The operating condition of these studies are typically the same, with operating temperatures ranging from 850 to 950 °C and at an average O 2 oxidant concentration of 21%.…”
Section: Design and Operational Issuesmentioning
confidence: 96%
“…Nowadays, it is still under rapid development and has been experimentally studied in the chemical, energy, and environmental industries for applications such as fluid catalytic cracking (FCC), fuel combustion and gasification, as well as pollutant emission reduction. Besides, with the increasing concerns about global warming, it is also a promising method for CO 2 capture when combined with the O 2 /CO 2 combustion technology. …”
Section: Introductionmentioning
confidence: 99%
“…Increasing the excess air resulted in an increase in NO emissions, while NO emissions decreased with increasing the scale of the air staging. Li et al 22 ,…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the excess air resulted in an increase in NO emissions, while NO emissions decreased with increasing the scale of the air staging. Li et al, 22 Duan et al, 23 and Daood et al 24 reported that NO emissions are much lower in oxy-fuel combustion than in air combustion. Shao et al 25 found that the average NO x concentration increased along with increasing oxygen concentration, and the maximum value and peak shape of the NO x concentration curve changed with temperature.…”
Section: Introductionmentioning
confidence: 99%